Time and punishment: new contexts and perspectives - Carr, Nicola; Robinson, Gwen (Palgrave studies in prisons and penology, 2022)
Chapter 1: Time and punishment: an introduction -- Chapter 2: Time, civilisation and ultimate penalities -- Chapter 3: Time and solitary confinement -- Chapter 4: Unmarking prison time during the covid-19 pandemic -- Chapter 5: Time in motion: transport between prisons as planned, lived and experienced time -- Chapter 6: The ‘reintegration paradox’: working towards the future while standing still -- Chapter 7: Time after time: imprisonment, re-entry and enduring temporariness -- Chapter 8: Probation work in the juridical field: a dance to the music of time -- Chapter 9: Criminal court time and social work time: pre-sentence reports and the chronotope of adjourned supervision.